The impact of inflation on income tax and social insurance contributions in Europe - Herwig Immervoll (University of Essex, Institute for Social and Economic Research (ISER), 2000)
Inflation can alter the characteristics of tax- and contribution systems in numerous ways. This paper demonstrates how inflation alters the distributive properties of nominally defined tax systems and looks at the impact of the tax revenues and social insurance contribution receipts generated. It provides quantitative estimates for Germany, The Netherlands and the UK, using a preliminary version of EUROMOD, a European tax-benefit microsimulation model. The integrated framework provided by the model permits the use of common income concepts across countries and therefore enables one to make informative comparisons of the distributive consequences of the inflation induced erosion of tax-band limits, thresholds, deductions, tax credits, etc. The paper also tests the performance of automatic indexing regimes used in two of the countries. – – Inflation kann zu Veränderungen der Eigenschaften und der Wirksamkeit von Abgabensystemen fuehren. Dieser Beitrag analysiert, wodurch und in welchem Ausmass Inflation die Verteilungs- und Aufkommenscharacteristiken von Einkommensteuer und Sozialversicherungsabgaben beeinflusst. Mithilfe einer Vorabversion eines neuartigen europäischen Steuer-Beihilfen Mikrosimulations-modells (EUROMOD) werden die quantitativen Auswirkungen in Deutschland, den Niederlanden und Grossbritannien untersucht. Das Modell erlaubt unter anderem die Verwendung identischer Einkommenskonzepte für die verschiedenen Länder. Dadurch werden informative Ländervergleiche hinsichtlich der Verteilungsauswirkungen einer inflationsbedingten Aushöhlung von Progressionsstufengrenzen, Frei-, Absetz- sowie Absetzbeträgen möglich. Der Beitrag analysisert ausserdem die Wirksamkeit der automatischen Steuerindexierungsverfahren, welche in zwei der betrachteten Ländern Anwendung finden.
Keywords: C81; H24; D31; 330; Inflation; Income Tax; Social Insurance Contributions; European Union; Microsimulation; Inflation; Einkommensteuer; Sozialversicherungsbeitrag; Simulation; EU-Staaten; Makroökonomischer Einfluss